The Role of Location and Cost in Individual Choices of Transportation Improvement Projects. - Swobodzinski, Martin; Jankowski, Piotr (Professional Geographer, 2015)
Transportation improvement programming is a process in which substantial resources are allocated to transportation infrastructure projects based on public input. This article reports on individual choice making in the context of a Web-based platform for public participation in transportation improvement programming. Based on the locations of the proposed transportation projects, we determined the extent to which the location and the cost of transportation projects informed individual choices regarding selections of road and transit projects. The presented analysis aims at uncovering factors that inform the choices of individuals in the context of transportation improvement programming along the dimensions of self-centered and selfless decision making. Such insight garners understanding of the requirements of and expectation toward Web-based public participation systems and participatory processes. Our results indicate a prevalence of preferences for projects within the vicinity of the individual’s home, work, and travel locations. In addition, the participants opted for project funding mechanisms under which regular residents, who might not benefit directly from a project, would pay more than the participants who selected the projects. These behavioral patterns evidence predominately self-centered choice-making behavior of participants in deliberation-centric, web-based transportation planning.